Picture Media and Chain Messages as Effective Strategies for Listening Learning in Elementary Schools - Kasmawati, Kasmawati (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2021)
The purpose of this study was to describe the use of media images and chain messages as an alternative strategy for listening learning in elementary schools. The learning design consists of three cycles: (a) The first cycle: matching the picture with the sound; (b) The second cycle: marking the images according to the storyline; and (c) The third cycle: chain messages. The results showed that one of the efforts to improve the quality of listening learning processes and outcomes in elementary schools was using picture media and chain messages. It is based on the indication that after this technique is applied in learning, student achievement increases as seen from adequate trials, higher learning quality than conventional techniques, and very positive student responses.